Mlodziez a sport wyczynowy. Psychohormonalne symptomy przetrenowania u mlodych kobiet - Obminski, Z.; Lerczak, K.; Blach, W. (Medycyna sportowa, 2003)
Material and methods. Seven female junior judoists were studied. Capillary blood was sampled in the morning from earlobes before an international tournament and, following preparations lasting several months, during European Championships on the following occasions: on the day preceding eliminations, on the following day of rest, and on the day preceding final competition (Day 3). Results. Mean concentrations of cortisol and testosterone on the day preceding European Championships were significantly (p < 0.05) lower than before the international tournament. A marked mood depression and lower cortisol levels were observed before the contests in 4 subjects who eventually lost their elimination competition, compared with those who passed to the finals. Conclusions. The four eliminated judoists exhibited a loss of training load tolerance over three weeks preceding European Championships, which resulted in a reduced adaptivity and in overtraining syndrome. This was expressed by markedly reduced cortisol concentrations and catastrophically perceived situation.